IMPLEMENTASI AI DALAM LAYANAN REFERENSI VIRTUAL PERPUSTAKAAN UPI: KESIAPAN DAN TANTANGAN - Damayanty; Susanti, Dian Arya; Yogaswara, Tri Agung (Pustakaloka, 2025)
Libraries in the digital era are experiencing significant transformation in services, especially reference services. As one of the college libraries in Indonesia, the Library of the Indonesian Education University (UPI) faces the challenge of transforming its virtual reference services through the implementation of artificial intelligence (AI). The purpose of this study is to identify the potential developments and challenges faced in transforming virtual reference services through the implementation of AI. The method used in this study is descriptive qualitative. The results of the study show that the readiness of UPI Library human resources in terms of knowledge and skills is already relevant to their educational background, and staff have the motivation to learn further. Readiness of technological infrastructure still requires improvement, particularly in server capacity and internet speed. The readiness of policies and management support, including leadership commitment to technological transformation, is strong; however, specific policies regarding new technologies still need to be formulated. Overall readiness assessment shows excellent potential for adopting AI in virtual reference services.